LAGU ANAK SEBAGAI MEDIA PENGEMBANGAN NILAI AGAMA DAN MORAL PADA ANAK USIA DINI DI KELOMPOK BERMAIN WADAS KELIR PURWOKERTO - Risdianto Hermawan; Siti Fatonah (IAIN Purwokerto, 2020)
This study discusses the development of religious and moral values ​​in early childhood through children's songs. The purpose of this research is to find out how children's songs can be used as a medium in developing religious and moral values ​​in early childhood in the Purwokerto Wir Kelada Play Group. Research conducted by researchers is field research, which is a method of research that is directly carried out by plunging into the field where data is collected. With qualitative data collection, the research is made by describing things that are examined using data in writing or verbally. Children's songs which are the creation or composition of the mother in the Wadas Kelir Play Group are applied through three stages, namely planning, implementation, and evaluation. Song lyrics used are adjusted to the level of child development and the culture of the surrounding environment. From the results of the analysis, children's songs used as learning media in the Wadas Kelir Play Group can develop religious and moral values ​​in early childhood.